A challenge to estimate global canned tuna demand and its impact on future tuna resource management using the gamma model. (May 2022) - Kawamoto, Taro
Abstract: The overall demand for canned tuna products has increased remarkably over the last four decades because it is a good nutritional source of protein with competitive prices and health benefits. This study focused on the top thirty countries that account for 99% of global consumption in recent years to estimate the global canned tuna demand by 2050, using a density function of gamma distribution (gamma model). We found five markets including the Asia, Central and South America, Africa, Oceania and Middle East were growing, although the other two markets including the EU and North America are maturing or matured. Additionally, we discovered a significant quadratic correlation between the average per capita GDP and canned tuna consumption per capita when looking at the world as a whole. We estimated the global canned tuna demand will continue to increase further over the next several decades, and will reach 2, 466, 000 t in 2050, about 34% increase compared to the current level. Yet global tropical tuna resources are improbable to accommodate the future canned tuna demand, as the canned tuna dominants (62%) in the global tropical tuna catch in recent years. In conclusion, challenges estimating the long-term canned tuna demand would contribute to the sustainable use of tuna resources, including the improvement of the current fishing management in the socioeconomic aspects of the harvest control rules for tuna Purse Seine fisheries which dominate raw material supplies for canned tuna production.